Evaluation of schools and improvement plans: Actions of the education inspectorate in Catalonia - Serentill i Rubio, Josep (Avances en Supervisión Educativa, 2023)
The Education Inspectorate in Catalonia has a long tradition of external evaluation of schools, which it has been consolidating and improving through various instruments, which have evolved through various implementation campaigns. Without intending to be exhaustive, we can cite tools such as the Focused Evaluation (EF), the Database of Quality References (BDRQ), the School Indicator System (SIC), the Global Evaluation of Schools (AGD), the Evaluation Annual Schools (AVAC), the Evaluation of Educational Innovations (AVIE).
Keywords: External school evaluation; self-evaluation; school autonomy; educational indicators; educational inspectorate; evaluation criteria educational quality; accountability